2016
DOI: 10.18632/oncotarget.12190
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-98 acts as a tumor suppressor in hepatocellular carcinoma via targeting SALL4

Abstract: MicroRNAs (miRs) are involved in the development and progression of hepatocellular carcinoma (HCC), but the regulatory mechanism of miR-98 in HCC still remains unclear. Here we found that miR-98 was significantly downregulated in HCC tissues compared to matched adjacent normal tissues (ANTs). Low miR-98 expression was associated with tumor size, metastasis, portal vein tumor embolus, and poor overall survival. Ectopic expression of miR-98 decreased the proliferation, migration, invasion and epithelial-mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 42 publications
1
48
0
Order By: Relevance
“…miR-98 is a tumor suppressive miRNA, knockdown of which leads to a reduction of 1,25-vitamin D anti-growth effect of prostate cancer and overexpression of miR-98 suppressed prostate cancer cell growth (23). miR-98 inhibits human ovarian cancer stem cell proliferation via retinoblastoma-associated protein-E2F transcription factor pathway and suppresses hepatocellular carcinoma by targeting Sal-like protein 4 and collagen triple helix repeat containing 1 (24)(25)(26). Currently, a limited amount of data is available regarding miR-98-mediated regulation of osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…miR-98 is a tumor suppressive miRNA, knockdown of which leads to a reduction of 1,25-vitamin D anti-growth effect of prostate cancer and overexpression of miR-98 suppressed prostate cancer cell growth (23). miR-98 inhibits human ovarian cancer stem cell proliferation via retinoblastoma-associated protein-E2F transcription factor pathway and suppresses hepatocellular carcinoma by targeting Sal-like protein 4 and collagen triple helix repeat containing 1 (24)(25)(26). Currently, a limited amount of data is available regarding miR-98-mediated regulation of osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs function as specific gene regulators by interacting preferentially with the 3' untranslated region (3'UTR) of their target genes in a base-pairing manner, and subsequently inducing mRNA degradation or translational repression (7). To date, various miRNAs have been investigated that may serve important roles in diverse biological processes, such as cell proliferation, viability, apoptosis, cell cycle, angiogenesis, invasion, motility and differentiation (8)(9)(10). A previous study reported that >50% of known miRNAs are located at genomic regions or in fragile sites closely correlated with cancer (11).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these mesenchymal markers also contribute to cell stemness, for example, Snail inducing CD44 high CD24 low CSC population 34 and ZEB1 inducing tumorinitiating capacity in pancreatic and colorectal cancer cells. 35 36 and esophageal squamous cell carcinoma. 37 Tian group predicted, through bioinformatics analysis that "GTGG" was one of the putative binding sites of SALL protein family.…”
mentioning
confidence: 99%